Analysis and Graphical Expression of Vitality Spatial Planning for a Lowland Healthy Campus Community - J.R SHI; X.M. Zhao; Y.Y. Zhang (International Association of Lowland Technology, 2021)
ABSTRACT: On the basis of combing related theories of the vitality of the existing public space and summarizing the five indexes of the vitality of public space, the author designs questionnaire survey, in which participants evaluate the importance of each index in campus activity space and collects relevant information about spatial cognition. The survey found that the overall user considered all five indicators to be important. Empirical analysis is made to quantify the content of the five evaluation indexes of campus space characteristics, and to analyze the influence of space environment characteristics on the outdoor activities of the users. By establishing the correlation mathematical model, we can conclude that the change of spatial vitality index (independent variable) can affect the user's behavior activity (dependent variable), and then we can get the quantitative calculation method of campus public space vitality.